Study of automatically generate test data based on evolutionary algorithm method - Zhag yunlong; Ni Jian (Institute of Advanced Engineering and Science, 2014)
The study of automatically generate test data based on evolutionary algorithm method focuses on the path coverage direction. The key problem is how to construct a suitable and has a good orientation of the fitness function to evaluate the quality of a test data. This paper introduces several evolution test methods, shows its advantages and problems it can effectively solve, and proposes an improved evolutionary test data generation method, which can generate better test data. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3342